Household food insecurity and its association with self-reported male perpetration of intimate partner violence: a survey of two districts in central and western Uganda. Issue 3 (31st March 2021) - Awungafac, George; Mugamba, Stephen; Nalugoda, Fred; Sjöland, Carl Fredrik; Kigozi, Godfrey; Rautiainen, Susanne; Malyabe, Robert Bulamba; Ziegel, Leo; Nakigozi, Gertrude; Nalwoga, Grace Kigozi; Kyasanku, Emmanuel; Nkale, James; et al.
Abstract : Objectives: This study aimed to determine the lifetime prevalence of male-perpetrated intimate partner violence (IPV), and to assess the association with food insecurity, sociodemographic factors and health risk behaviours in Uganda in the year preceding COVID-19-associated lockdowns. Design: Population-based, cross-sectional household survey. Setting: Urban, semiurban and rural communities of the Wakiso and Hoima districts in Uganda. Participants: A total of N=2014 males aged 13–80 years participated in the survey. The current study included males who reported having ever been in a sexual union and responded to the IPV questions (N=1314). Measures: Data were collected face-to-face from May 2018 to July 2019 using an interviewer-mediated questionnaire. Lifetime IPV perpetration was measured as 'no physical and/or sexual IPV', 'physical' versus 'sexual violence only', and 'physical and sexual violence'. Past-year food insecurity was measured through the Food Insecurity Experience Scale and categorised into 'none', 'low' and 'high'. Multinomial logistic regression was used to determine the crude and adjusted relative risk ratios (aRRRs) of IPV perpetration in relation to self-reported food insecurity, adjusting for sociodemographic and health risk behaviours. Results: The prevalence of self-reported lifetime IPV perpetration was 14.6% for physical and 6.5% for sexual violence, while 5.3% reported to have perpetrated both physical and sexual IPV. Most (75.7%) males reported no food insecurity, followed by low (20.7%) and high (3.6%) food insecurity. In adjusted models, food insecurity was associated with increased risk of having perpetrated both physical and sexual violence (aRRR=2.57, 95% CI 1.52 to 4.32). IPV perpetration was also independently associated with having had more than one lifetime sexual partner and drinking alcohol, but not with education level or religion. Conclusion: This study suggests that food insecurity is associated with male IPV perpetration, and more efforts are needed to prevent and mitigate the expected worsening of this situation as a result of the COVID-19 pandemic.